Assessment of Clinical Barriers Factors to Healthy Lifestyles amongst Hypertensives in Communities of Idoma Tribe of Benue State, Nigeria - Daniel Okpe; Regidor Dioso; Ogunyewo Abayomi; Oyerele Emmanuel; Daniel Grace (Clinical and Research Journal in Internal Medicine, 2023)
Background: Some personal and health-related factors may influence hypertensive patients' level of self-management. Aim: to determine clinical factors acting as barriers to the eleven (11) healthy lifestyles (self-management) practices amongst hypertensives in communities of Idoma tribe, Benue state Nigeria. Methods: A multi-stage, multi-communities, cross-sectional simple random sampling method for quantitative and qualitative data using Self-reported/administered questionnaire and Semi- structured focus group discussion/interviews was used. Data analyzed using descriptive statistics-frequency and percentage presented in tables, while thematic analysis was used for qualitative information. Results: Clinical factors barrier to medication adherent are; not having any symptom 85.1%, fear of side effect of drugs 84.4%, physical exercise barriers are Physician did not prescribe physical exercise 86.1%, Not have any symptoms 85.7%; Respondent stated that feel better 84.9% and when you do not have any symptom 79.9%, are barriers to self- BP monitoring clinically. Feel better 88%, poor commitment between patients and health care personnel 76% are barriers to DASH. 86% and 74.2%, feel better, being overweight were weight management barriers respectively. Moderation in Alcohol clinical factor barriers are; when you feel well 75.7% and feel better 72.6%. Barrier factor to non-smoking adherence is feel better 58.4%. Stress control clinical barriers are; feel worse 73.5% and multiple medical treatment regimen 71.8% amongst others. Follow prescribed treatment plan; Feel better 84%, not having symptom 81% amongst others were clinical barriers. Conclusion: The result calls for intervention to improve the population clinical factor barriers to the eleven healthy lifestyles variables.